FRI0412 B cell depletion ameliorates tissue fibrosis through regulating macrophage differentiation in a bleomycin-induced systemic sclerosismodel mouse. (12th June 2018) - Numajiri, H.; Yosizaki, A.; Fukasawa, T.; Ebata, S.; Asano, Y.; Sato, S.
Abstract : Background: B cells play a critical role in pathogenesis of autoimmune diseases through various functions such as cytokine production and induction of other immune cell activation. Recent studies have shown the efficacy of B cell depletion therapy with rituximab, a human CD20 chimeric monoclonal antibody, in systemic sclerosis (SSc) patients. However, it still remains unclear why B cell depletion can be effective for SSc. Objectives: The purpose of this study is to assess the role of B cell depletion in SSc. We evaluated the skin and lung fibrosis of bleomycin (BLM)-induced SSc model mice treated with B cell depletion. Furthermore, we investigated effects of B cell depletion on T cells and macrophages. Methods: To generate BLM-induced SSc model mice, 200 µg of BLM was injected subcutaneously to C57BL/6 mice every other day for 4 weeks. Anti-mouse CD20 monoclonal antibodies, which can deplete mouse B cells, were also injected every 2 weeks from either one week before (the pre-depletion group) or 2 weeks after (the post-depletion group) BLM treatment. After 4 weeks of BLM treatment, skin and lung fibrosis was assessed histopathologically. To examine the effect of B cell depletion on T cells and macrophages, purified B cells were cultured with T cells or macrophages and then T cell cytokine production and macrophage phenotype were analysed. Results: Skin and lung fibrosis increased in BLM-induced SSc mice. In the coculture experiments, B cells from BLM-induced SSc mice promoted differentiation of T cells producing fibrogenic cytokines such as interleukin-4 compared with control B cells, while they inhibited regulatory T cell (Treg) differentiation. Skin and lung fibrosis was inhibited in both pre- and post-depletion groups with the inhibition greater in the pre-depletion group than in the post-depletion group. Despite the finding that greater fibrosis remained in the post-depletion group than in the pre-depletion group, the post-depletion group showed significantly higher frequencies of Treg compared with the pre-depletion group. Furthermore, the post-depletion group also exhibited lower fibrogenic cytokine-producing T cell frequencies, suggesting that the change in T cell cytokine production could not account for the more strongly reduced fibrosis observed in the pre-depletion group. Therefore, we examined other immune cell response to B cell depletion. Recent studies have revealed that macrophages are divided into two subtypes: M1 and M2 and that M2 macrophages show fibrogenic effects in SSc. This study showed that macrophages cultured with B cells from BLM-induced SSc mice exhibited enhanced M2 differentiation compared with control B cells. Remarkably, frequencies of M2 macrophage with fibrogenic capacity significantly decreased in the pre-depletion group compared with the post-depletion group, which could account for the more strongly inhibited tissue fibrosis in the pre-depletion group. Conclusions: Our results indicate that therapeutic effects of B cell depletion on tissue fibrosis exert through regulating macrophage differentiation rather than T cell cytokine production in SSc, first demonstrating that interaction between B cells and macrophages in development of fibrosis in SSc. Disclosure of Interest: None declared